Escherichia coli K-12 mutation that inactivates biodegradative threonine dehydratase by transposon Tn5 insertion. - Goss, T J (1984)
From a collection of kanamycin-resistant mutants of Escherichia coli K-12 isolated by transposon Tn5 mutagenesis, we have identified a mutant that lacks functional biodegradative threonine dehydratase (EC 4.2.1.16) by direct enzyme assay and by the loss of cross-reacting material with affinity-purified antibodies against the purified enzyme. Aerobic and anaerobic growth of this strain on various carbon sources failed to reveal a phenotype. Evidence for the insertional inactivation of threonine dehydratase by Tn5 was obtained by cloning the DNA segments flanking the Tn5 insertion site into pBR322 and hybridizing the cloned DNA to a synthetic oligodeoxynucleotide probe complementary to the DNA segment coding for a unique hexapeptide at the amino terminus end of the enzyme; the region of homology to the synthetic cDNA sequence appears to be located within about 500 nucleotides from one end of Tn5. Genetic analysis with the transposon element that caused insertional inactivation located the tdc gene at min 67 on the E. coli chromosome.